Pendekatan Integratif Bimbingan Konseling Islam Berbasis Al Qur'an dalam Pembentukan Karakter Religius Remaja: Perspektif Nilai-Nilai Qur'ani dalam Akhlak dan Kepribadian - Nelda Novita; Irsyadunnas (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aims to explore the implementation of Al-Qur’an-based Islamic counseling guidance in shaping the religious character of adolescents. This approach integrates Qur’anic values as moral and spiritual foundations to support adolescent development during critical phases of life. Using a literature review method, this research examines relevant theoretical perspectives, concepts, and previous findings related to Islamic Counseling Guidance and religious character formation. The analysis focuses on Qur’anic values such as faith, piety, patience, and honesty, which serve as fundamental principles for building noble character and responsible personality among adolescents. The results indicate that Al-Qur’an-based counseling is effective in internalizing Islamic teachings into adolescents’ daily lives, enabling them to overcome emotional, social, and spiritual challenges, while simultaneously strengthening their spirituality. Moreover, this research highlights the important roles of family and surrounding environment as supporting factors in the development of religious character. Overall, this approach provides a comprehensive solution by not only emphasizing cognitive aspects but also integrating spiritual and emotional dimensions, enabling adolescents to deal with life challenges with better attitudes and deeper religious awareness.